"It's sort of like being a detective": Understanding how Australian men self-monitor their health prior to seeking help - Braunack-Mayer Annette; Smith James A; Wittert Gary; Warin Megan (BMC, 2008)
Abstract Background It is commonly held that men delay help seeking because they are ignorant about and disinterested in their health. However, this discussion has not been informed by men's lay perspectives, which have remained almost entirely absent from scholarship relating to men's help seeking practices. Methods In this qualitative paper, we draw on semi-structured interviews with 36 South Australian men to examine their understandings of help seeking and health service use. Results & Discussion We use participants' talk about self-monitoring to challenge the assumption that men are disinterested in their health, arguing instead that the men in our study monitored their health status and made conscious decisions about when and how to seek help. Using an inductive approach during the thematic analysis we were able to identify four key factors that influenced how men monitored their health and explain how these intersect with the way men sought help and used health services. Conclusion We show that the men in our study were actively engaged in the self-monitoring of their health. We suggest that these findings offer an alternative approach for understanding how we can promote men's interaction with health services.